Best practice in primary care pathology: review 6. Issue 3 (5th July 2006) - Smellie, W S A; Forth, J; Coleman, J J; Irvine, W; Dore, P C; Handley, G; Williams, D G; Galloway, P J; Kerr, K G; Herriot, R; Spickett, G P; Reynolds, T M
Abstract : This sixth best practice review examines four series of common primary care questions in laboratory medicine: (1) laboratory monitoring in hypertension and heart failure abnormalities; (2) markers of inflammatory joint disease; (3) laboratory investigation of chronic diarrhoea; and (4) mumps and chickenpox. The review is presented in question–answer format, referenced for each question series. The recommendations represent a precis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus based rather than evidence based. They will be updated periodically to take account of new information.